Analysis of the Implementation Green Accounting and Material Flow Cost Accounting on Corporate Sustainability - Dwi RT, Dita Rari; Heryana, Toni; Basuki, Teguh Iman (Program Studi Akuntansi FPEB UPI, 2024)
Corporate sustainability, or company sustainability, is a concept that adopts a long-term business orientation to meet the needs of present and future stakeholders while considering aspects of economic growth, environmental protection, and social justice. This research aims to determine the influence of the implementation of green accounting and material flow cost accounting on corporate sustainability in industrial companies listed on the Indonesia Stock Exchange (IDX) during the 2022 period. This study is quantitative research with a sample selection technique using purposive sampling. The hypothesis testing conducted consists of multiple linear regression analysis, determination coefficient (R2) test, and t-statistic test using Wrap-PLS version 8.0. The research results show that green mental flow cost accounting has an effect of 18.3% on corporate sustainability, while green accounting has no effect.